Intestinal uptake of barley protein-based nanoparticles for β-carotene delivery - Guangyu Liu; Ying Zhou; Lingyun Chen (Elsevier, 2019)
Our previous study introduced a barley protein microparticle for encapsulation of hydrophobic drug/nutraceutical, which could release nanoparticles upon gastric digestion and deliver encapsulated compound to a simulated intestinal environment intact. This work focused on evaluating the potential of liberated nanoparticles to improve the absorption of encapsulated compounds (e.g., β-carotene) using in vitro Caco-2 cell and ex vivo small intestine models. Nanoparticles obtained from gastric digestion of barley protein microparticles had a spherical shape and an average size of 351 nm. Nanoparticles showed low cytotoxicity in Caco-2 cells and their cellular uptake was dependent on time, concentration and temperature. In a Caco-2 cell monolayer model, significantly greater uptake and transport of β-carotene were observed when it was delivered by nanoparticles (15%), compared to free β-carotene suspension (2.6%). In an ex vivo rat jejunum model, nanoparticles showed the capacity to retain in small intestinal tissue. Approximately 2.24 and 6.04 μg nanoparticle were able to permeate through each cm2 intestinal tissue and translocate to the serosal side after 60 and 90 min, respectively. Results from this study demonstrated the absorption improving effect of the barley protein nanoparticles and suggested their potential as vehicles for hydrophobic compounds. KEY WORDS: Barley protein, Nanoparticles, Hydrophobic, Caco-2 cell, Intestinal transport